ANALISIS KESULITAN GURU SEKOLAH DASAR DALAM MENGEMBANGKAN INSTRUMEN ASESMEN HIGHER ORDER THINGKING SKILLS - Maryono; Eka Sastrawati; Hendra Budiono (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
This article analyzes elementary school teachers’ difficulty in developing higher-order thinking skills assessment instruments. This implementation will describe the difficulties faced by teachers, especially elementary school teachers in developing higher-order thinking skills assessment instruments. The research was a qualitative approach with a case study research. The subject of the research involved three fifth-grade elementary school teachers of SDN 018/V Kuala Tungkal. Data collection techniques were observation, interviews, and documentation. The data collection instruments used were observation, interview, and documentation sheets. The results of the research indicated several main points that were elementary school teachers’ difficulties in developing higher-order thinking skills assessment instruments including teachers' understanding of operational verbs in HOTS, teacher adjustment of basic competencies and indicators in arranging lesson plans, teacher difficulties in arranging HOTS assessment instruments, and time management in arranging the HOTS assessment instrument. These difficulties influence the students not to be used to their critical thinking in solving problems that are based on daily life problems.